Long term outcomes of 20G versus 23G pars plana vitrectomy in the treatment of traumatic macular hole - Al Rubaie, Khalid (2014)
Purpose: To compare the long-term results of 23- and 20-gauge pars plana vitrectomy (PPV) for traumatic macular hole (TMH) Methods: A retrospective, comparative case series of 29 consecutive eyes of 29 patients with TMH that underwent either 23- or 20-gauge PPV was conducted. The main outcome measure was the anatomical closure rate following surgery. Results: Among 29 patients, 6 (20.8%) were younger than 16 years. Twenty-five patients (86.2%) were males. Twenty gauge PPV was performed in 16 eyes (55.2%) and 23-gauge PPV was performed in the remaining 13 eyes (44.8%). Dye-assisted internal limiting membrane peeling was performed in all but 3 (10.3%) eyes. Anatomical failure was seen in a total of 11 eyes (37.9%). Among those, 6 eyes (54.4%) were in the 23-gauge PPV group and 5 (45.6%) in the 20-gauge PPV group. The success rate was not statistically significantly different between the two groups. None of the eyes developed retinal breaks or detachment. Conclusions: Twenty three-gauge PPV has a similar success rate to twenty-gauge PPV in TMH.